Effects of low-pressure EGR on gaseous emissions and particle size distribution from a dual-mode dual-fuel (DMDF) concept in a medium-duty engine. (25th December 2019) - Macián, Vicente; Bermúdez, Vicente; Villalta, David; Soto, Lian
Highlights: The EGR rate is the key to the dual-mode dual-fuel concept development. The NOx and PM emissions are lower at dual-mode dual-fuel than conventional diesel. Increasing EGR increases the accumulation-mode particles at dual-mode dual-fuel. At high loads, the EGR increases the accumulation-mode particles at dual-mode dual-fuel. At low load, the nucleation-mode particles and HC emission increases at dual-mode dual-fuel. Abstract: The application of a low-temperature combustion concept, such as RCCI combustion under real engine operating conditions is extremely complex. However, the implementation of the dual-mode dual-fuel (DMDF) strategy allows operating in low-medium load with the RCCI combustion and in high load with dual-fuel diffusive combustion. This allows taking advantage of the benefits of RCCI combustion as the simultaneous reduction of PM and NOx emissions. However, there are still serious challenges that required to solve, such as the high-pressure rise rate and the excessive CO and HC emissions. In this sense, this work shows how the implementation and an adequate adjustment of the cooled LP-EGR rate significantly minimize these problems and also shows how the LP-EGR has a greater impact on the DMDF than on the CDC concept. This work has been performed in a modern medium-duty diesel engine fueled with standard gasoline and diesel fuels, with which a cooled LP-EGR loop has been coupled. A TSI Scanning Particle Sizer (SMPS 3936L75) was used to measure the particles size distribution and the Horiba MEXA-ONE-D1-EGR gas analyzer system to determine gaseous emissions. A parametric variation of the LP-EGR rate was experimentally performed to analyze the effect over each combustion process that encompasses the DMDF concept (fully premixed RCCI, highly premixed RCCI and dual-fuel diffusion) and its consequent impact on gaseous and particle emissions. In addition, results were compared against the CDC concept to state the benefits of the DMDF concept. Among the different results obtained, it can be highlighted that during the RCCI strategy the increase in LP-EGR rate provided a reduction in NOx emissions. Nonetheless, unlike that fully premixed RCCI in highly premixed RCCI combustion, the PM emissions increased with this increment in the LP-EGR rate, shifting the size distribution of particle toward larger sizes, but decreasing the HC and CO emissions. Finally, with the exception of the high HC and CO emissions in fully premixed RCCI, in all the combustion strategies of the DMDF concept, a reduction of the analyzed pollutants was observed when compared with the CDC mode.